Self-assessment of Polish pharmacy staff’s readiness to promote health - Bojar, Iwona (Int J Clin Pharm, 2020)
Background Nowadays, pharmacists are expected to focus not only on dispensing medicines but also on the wellness of the patient. In some developed countries a pharmacist is clearly defined as a health care professional that can make a contribution to improving the general health of the population. Objective To assess the readiness of Polish pharmacy staff to engage in health promotion and educational activities. Setting Community pharmacies in Poland. Method The study group consisted of 308 pharmacy staff (248 pharmacists and 60 pharmacy technicians) employed in Polish pharmacies. The survey questionnaire referred to three domains: systemic solutions for health promotion, readiness of pharmacy staff as a professional group to promote health, personal readiness to promote health. Responses about pharmacy staff’s readiness to promote health were scored using a 10-point scale. Scale reliability for all items (overall readiness), and for items within the three domains separately, were tested using Cronbach’s α and average inter-correlation coefficient among the items. Main outcome measure Pharmacy staff’s readiness to promote health (the questionnaire containing 32 items). Results The overall readiness of pharmacy staff to promote health was rather low (average of 4.6 ± 1.5 in 1–10 scale). The highest scores were obtained for pharmacy staff’s personal readiness to promote health (average of 5.5 ± 1.8) which was neutral on the scale. The lowest scores were obtained for systemic solutions for health promotion (average of 3.6 ± 1.4). Readiness of pharmacy staff as a professional group was ranked in the middle (average 4.8 ± 1.8). Surveyed pharmacy staff rated their readiness to promote health in the work environment significantly higher than promoting health in the local community. Female and younger pharmacy staff as well as those with job seniority of less than 5 years, or pharmacy technicians assessed their readiness to promote health significantly higher than others. Readiness to promote health was higher among pharmacy staff working in pharmacies employing up to 3 staff members and at pharmacies with over 200 customers daily. Conclusions The overall readiness of pharmacy staff to promote health was low, especially in the domain of systemic solutions in health promotion.